The pathogens and curative effects analysis of perianal abscess of infants under 3 months - Yimin Zhu; Fuying Xu (The Turkish Journal of Pediatrics)
In order to guide clinical treatment for perianal abscess of young infants, the characteristics of pathogens and curative effects analysis were conducted. Bacterial culture results, antibiotics susceptibility tests and curative effects of abscess incision were retrospectively analyzed in 66 cases of perianal abscess of infants under 3 months. There were 48 cases of Klebsiella pneumoniae, 7 cases of Staphylococcus, 6 cases of Escherichia coli, 5 cases of Proteus in the pathogen culture results. Klebsiella pneumoniae, the predominant pathogen, was susceptible to most antibiotics, especially to imipenem, cefoperazonesulbactam and amikacin with low drug resistance rates. However, high drug resistance rates were found to ampicillin and nitrofurantion. After abscess incision, the complication rate of anal fistula was 6.6％ in infants under 3 months and 60.3％ in the adult group. There was significant difference P＜0.01. In conclusion, Klebsiella pneumoniae was the most common pathogen in perianal abscess of infants under 3 months and was commonly resistant to ampicillin and nitrofurantion. Since perianal abscess of infants under 3 months is a self-limited disorder, simple surgical intervention and synchronous sensitive antibiotic administration are suggested as the optimal management.